Knowledge and Health Care Seeking Behaviours on Cancer of the Cervix among Rural Women- A Case Study of Isingiro District - Aheisibwe, Hillary; Akankwasa, Gilbert; Twesigomwe, Godfrey; Agaba, Collins; Baguma, Edwin; Tibatemwa, Diana; Ntaro, Moses (Journal of Health, Medicine and Nursing, 2015)
Cervical cancer is an abnormal growth of cells in the cervical region of the uterus. Cancer of the cervix occurs when the cells of the cervix change in a way that leads to unregulated growth and invasion of other tissues or organs of the body. Cancer of the cervix is the most common cancer affecting women in Africa and in the developing countries, second only to breast cancer worldwide(Franco et al 2003). Very few studies on knowledge and health care seeking behaviors have been carried out among women living in rural areas in Africa. Cervical cancer has threatened the lives of women in Uganda leading to other associated long-term problems in families. Aim: This study was intended to assess the knowledge of cervical cancer and the related health care seeking practices among the rural women in Isingiro district, south-western Uganda. Methods: It was a community based cross sectional study, involving women of 18 years and above. The study participants were first given an explanation of the study and thereafter, a questionnaire was administered for data collection. The sample size estimated using the formula: N= Z2p (1-p)/ e2. Results: According to the study, the knowledge, prevalence of symptoms and predisposing factors to cervical cancer was at 4.62 %( 18/385) and 0.00 %( 0/385) respectively. The study also revealed that; 98.35% (374/385) would accept CaCx screening, 0.33 %( 01/385) had utilized cervical cancer screening facilities and that 97.02 %( 374/385) did not screen due to lack of knowledge on CaCx. There is need to conduct a community based study to know the practices of health workers and assess if they are educating and offering suggestions for screening for cancer of the cervix. The research therefore recommends intervention the relevant stakeholders in the health care system to demystify facts on this disease among rural women, especially in Isingiro district.
Keywords: Cancer of the Cervix; Knowledge; Health care seeking behaviours